Kajian Tekstual The Drupadi Trilogy Karya Ananda Sukarlan - Nirai Nathalia Deasy Kristiana (Universitas Gadjah Mada, 2016)
The Drupadi Trilogy is Ananda Sukarlan’s music composition based on the story aboutDrupadi from Mahabharata. Aside from using the narrative literature, Sukarlan alsoused the music elements from Balinese gamelan in his art music composition. Therefore,by using the theory of Tripartition (Jean-Jacques Nattiez) and the theory of musicinterrelation (Philip V. Bohlman), The Drupadi Trilogy was analyzed textually to explainthe occurrence of elements of Balinese gamelan music in the composition, the connectionand correlation between the composition with other elements, and the purpose behindtheir connection and correlation.